WOCAT SLM Technology: “Drought Tolerant Barley Variety: 'Kounouz' [Tunisia]” - Rudiger, Udo; Ben Ghanem, Hajer; Zaiem, Anis; Frija, Aymen; Dhehibi, Boubaker; Idoudi, Zied (The Global Database on Sustainable Land Management (SLM) of WOCAT, 2023)
The introduction of 'Kounouz,' a drought-tolerant barley variety, has significantly enhanced farm income and reduced production risks for small-scale farmers in Tunisia. Tunisia has a semi-arid climate with annual precipitation ranging between 200 and 450 millimeters. Many people are dependent on the agricultural sector. Typically, barely is cultivated and used for fodder or sale. Barely production is increasingly in danger for failures because of droughts caused by climate change. Therefore, a new and drought tolerant barley variety was sought. NARS developed such seed by using the germplasm that was made available by the International Center of Agricultural Research in Dry Areas (ICARDA). The benefits of 'Kounouz' encompass enhanced farm income through reduced production risks and increased yields. The adoption of this approach has already made significant strides. By 2019, approximately 617 tons of certified seeds were available. This accomplishment was the result of a successful collaboration between a large-scale cooperative, “Societe Mutuelle Centrale de Semences” (COSEM), and a private seed company, “Société Tunisienne de Fertilisation et d'Irrigation” (Tunifert). Presently, two more cooperatives, namely “Société des Semences Séléctionnées” (SOSEM) and “Coopérative Centrale des Semences et des Plants Sélectionnés” (CCSPS), have also become actively involved. It is worth noting that a mere 5% of the Kounouz seeds are estimated to be sourced from certified suppliers, with the majority being multiplied on individual farms. Consequently, it is estimated that the cultivation of Kounouz now spans over 20,000 hectares.